The Existence Of Overall Satisfaction In Service Customer Relationships - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Garbarino Johnsol X99) fired that there is no correlailo between overall satbArction and loyalty in the field of customer relationship. Their,findhsg indicates that satisfactiolt is na longer an important issue in managing serPice orgemizations. This research hivesiigates the existence of sr.:lb.-pm:Hon iri serk,ice orvanizastans, which have relationships with customers. Contrary so Garbarino and Johnson's 11999) lindiorg, this research finds that overall satiVaction. through commitment, has a relationship with loyalty. flpnce, customer satisfixtion is still a main issue with respect to managing service 02` gani:.....ationsr especially service orydnizations !hat have mest6m.er-relnlionshfp strategy. Survey method was Conducted to test 12 hypotheses, and Me saonple (af this research is customers of credit cir,a-dhcnrders and supermarket cardizo!ders, Sample size is 382 consisting of 19+51,51.3%1 credit cardholders and 186 148:7%) superonarket cardholders. Data were anal-yzed using two-step structural equation modelling technique- in addition. this research also shows that invesiiNators and managers should pay allentinn to affects, because affecis have a unique role in relationship customer behavior